Analysis Of The Ultrasonic Cautery - Lee, Han Wei (Universiti Sains Malaysia, 2018)
Thermal cautery is a device used by surgeon in surgical operation to replace scalpel and to mitigate bleeding. The most popular cautery that used today is electrocautery. For the electrocautery, the current design of the thermal cautery facing safety issues while using it. One of the solution is introducing the ultrasonic technology in cautery. Both the usage of the electrocautery and ultrasonic cautery is compared show that the ultrasonic cautery has its advantages of safety features and has lower side effect to the patient after the surgery although the electrocautery has the advantages of cheaper in price, lighter and easier in maintenance. The information on the technology and working principle on the design of ultrasonic cautery does not given in any source thus the research and analysis on the technology and working principles of an ultrasonic cautery is important before any design work or improvement can be done. A review on the current design of the ultrasonic cautery has been done and it shows that most ultrasonic cautery need to be operate between 20kHz to 60kHz.Piezoelectric is used as the actuator to produce ultrasonic frequency due to its popularity in usage and has relative simpler usage. The control system to control the piezoelectric actuator is set up to control the piezoelectric actuator. The principles involve in a piezoelectric actuator is studied and experimented. Then amplification mechanism to amplify the amplitude of a piezoelectric actuator which has only 5